Prevalence and Risk Factors of Human Papillomavirus Infection in Asymptomatic Women in a Venezuelan Urban Area - Núñez-Troconis, José; Delgado, Mariela; González, Julia; Mindiola, Raimy; Velásquez, Jesvy; Conde, Betty; Whitby, Denise; Munroe, David J (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The purpose of this study was to investigate the prevalence and risk factors of genital human papillomavirus (HPV) infection in asymptomatic women, using the HPV DNA Hybrid Capture 2 (HC2) test. Three hundred and two women who attended the Out-Patient Gynecological Clinic of a tertiary level hospital, in a Venezuelan urban area, were selected for the study. A pap smear, a cervical swab for HC2 and gynecological exam were performed to each patient. The HC2 testing showed that 47 samples (15.6%) were positive to HPV. Forty patients (13.2%) were positive to high risk-HPV (HR-HPV) and 11 (3.6%) were positive to low-risk-HPV (LR-HPV). The prevalence of HPV infections was higher for women under 35 years (51.1%; p < 0.02), and decreased to 6.4% for women Â³ 65 years old. Women who had not finished high school had a higher prevalence of HPV infection (p < 0.035). Twenty six (42.6%) of 61 pathological Pap smears were positives to HPV infection. A statistically significant difference was found when HPV infection was compared in normal and abnormal Pap smear (HSIL+LSIL; p<0.0001). Twenty four of 56 (43%) women with diagnosis of LSIL, and 2(40%) of 5 with diagnosis of HSIL were positive for HPV infection. A statistically significant difference was found when we compared HPV infection in negative Pap smears and those with LSIL (p<0.001). The present study found that the prevalence of HPV infection in asymptomatic Venezuelan women who attended a tertiary level hospital was 15.6%. HPV infection was more frequent in young adult, and in women with low educational level